Searching for a non toxic natural insecticide from Pombalia bigibbosa (Violaceae) extracts against Tribolium castaneum (Herbst) - Ingrid María Cufre; Verónica Paola Tarcaya; Paula Gladys López; Jorge Miño; Sandra Viviana Clemente; Adriana María Broussalis (Dominguezia, 2025)
At the moment, there is growing concerned about the negative effects on human health, and the environment due to the widespread and indiscriminate use of conventional insecticides. For that reason, obtaining and characterizing new molecules of plant origin with insecticidal activity is, currently, one of the main research focuses for pest control.  Pombalia bigibbosa (Violaceae), native species for the Argentinian flora, is known in Brazil as canela-de-veado. In this study the insecticidal activity of dichloromethane, 50% EtOH, and tannin-free 50% EtOH extracts of P. bigibbosa was evaluated on T. castaneum, stored grain pest. The composition of the tannin-free 50% EtOH extract was analyzed by HPLC. Also, the effects of these extracts on the central nervous system were assessed. The 50% EtOH and tannin-free 50% EtOH extracts showed significant lethal and sub-lethal effects on T. castaneum larvae. Compounds with an HPLC elution profile similar to cyclotides were observed through HPLC analysis. Lastly, these extracts exhibited no effects on the central nervous system.